2020
DOI: 10.3390/molecules25184233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel 2-(Isopropylamino)thiazol-4(5H)-one Derivatives and Their Inhibitory Activity of 11β-HSD1 and 11β-HSD2 in Aspect of Carcinogenesis Prevention

Abstract: Glucocorticoid metabolism at the tissue level is regulated by two isoenzymes 11β-hydroxysteroid dehydrogenase (11β-HSD), which mutually convert biologically active cortisol and inactive cortisone. Recent research is focused on the role of 11β-HSD1 and 11β-HSD2 as autocrine factors of tumor cell proliferation and differentiation. Herein, we report the synthesis of novel 2-(isopropylamino)thiazol-4(5H)-one derivatives and their inhibitory activity for 11β-HSD1 and 11β-HSD2. The derivative containing the spiro sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…The studies carried out for the previously obtained 2-aminothiazol-4(5 H )-one derivatives have shown that the inhibitory activity in relation to both 11β-HSD1 and 11β-HSD2 is influenced by the type of substituent at C 5 as well as the moiety attached to the amino group at C-2 [ 20 , 21 , 22 ]. Regardless of the type of the substituent in the amino group, the highest inhibitory activity in relation to 11β-HSD1 was demonstrated by compounds containing the spiro thiazole and cyclohexane ring system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies carried out for the previously obtained 2-aminothiazol-4(5 H )-one derivatives have shown that the inhibitory activity in relation to both 11β-HSD1 and 11β-HSD2 is influenced by the type of substituent at C 5 as well as the moiety attached to the amino group at C-2 [ 20 , 21 , 22 ]. Regardless of the type of the substituent in the amino group, the highest inhibitory activity in relation to 11β-HSD1 was demonstrated by compounds containing the spiro thiazole and cyclohexane ring system.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the tert -butyl group to the molecule resulted in a significant increase in the inhibitory activity towards 11β-HSD2 compared to the isopropyl group [ 22 ] for derivatives having a methyl and phenyl substituent at C-5 (compounds 3a and 3f ) and a decrease for the derivative with an ethyl group ( 3b ). However, a decrease in selectivity in the inhibition of 11β-HSD2 is observed compared to isopropyl-containing derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiazole derivatives are also found as new enzyme inhibitors, for example Biovitrum BVT-2733, Biovitrum BVT-14225, AMG-221, and Amgen 2922 can inhibit 11β-hydroxysteroid dehydrogenase type 1 (Figure 1) [22][23][24][25][26][27][28][29]. Our previous research has also shown that some of the thiazolone derivatives may be selective inhibitors over one of the 11β-HSD isoforms (Figure 2) [30][31][32][33][34]. On the other hand, a group of compounds of interest from the pharmacological point of view includes the adamantane (tricyclo [3.3.1.13.7]-decane) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…These include adamantine triazoles such as the Merck compound 544 [36], amides from Abbott [37,38], sulfone, sulfonamide [39], pyrrolidine carboxamide [40], and adamantyl ethanone derivatives [41]. Our previous research has also shown that some of the thiazolone derivatives may be selective inhibitors over one of the 11β-HSD isoforms (Figure 2) [30][31][32][33][34]. Our previous research has also shown that some of the thiazolone derivatives may be selective inhibitors over one of the 11β-HSD isoforms (Figure 2) [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%